Effect of off-axis bending on microstructural and transport properties of coated conductor tape. (8th December 2022) - Ries, R; Gömöry, F; Mošať, M; Kujovič, T; Hintze, C; Gil, P
Abstract: In this work, the changes in the microstructural and DC transport properties of coated conductor tape, deformed in helical form during the manufacturing of a round cable, were studied. The superconducting layer experienced both outward ('OUT') and inward ('IN') bending with respect to the round core (rod) at various lay angles and former diameters. The microstructure of a rare-earth barium copper oxide (REBCO) surface was observed using a scanning electron microscope. Direct transport measurements in liquid nitrogen were used to investigate the influence of the bending parameters on the DC transport properties. In the OUT configuration, cracks on the REBCO surface were formed at a diameter of 9 mm or less at a lay angle of 45°. The critical current of the tape started to degrade at a diameter of 10 mm or less. The investigation showed that cracks are formed in the direction following the rod axis. In the IN configuration, the measurements were performed at lay angles of 25°, 30°, 38°, 45°, 52° and 60°. The highest critical current retention and the lowest degree of damage on the REBCO layer were observed at a lay angle of 30°; in particular, the critical current visibly degraded at diameters as small as 3 mm, and defects were visibly observed at diameters of 2 mm. At lay angles higherthan 30°, the critical current degraded sooner (at higher diameters), and an increased density of defects in the form of 'protrusion lines' was observed. We found that the protrusion lines followed the preferential cleavage direction at approximately 80° to the tape length, independently of the lay angle used. By using a lay angle lower than 30°, the critical current degraded sooner; no protrusion lines were observed, but cracks were formed at the tape edges. For both bending configurations, the lower former diameters led to a higher density of defects on the REBCO surfaces accompanied by the degradation of superconducting properties.